Peran Pluralisme Agama Dalam Membangun Kebudayaan Serta Peradaban Masyarakat Islam - Abdul Mujib (LP2M Institut Agama Islam Negeri (IAIN) Kediri, 2020)
Religious pluralism is reused to popularize that a religious community has experienced the peak of the glory of an Islamic country. The supporting factors are described in this paper so that the religious community in the present era can learn to return to what it was in the heyday of Islam. The formation of civilization in Islam cannot be separated from the management of diversity carried out by the Islamic government in the past. The practice of pluralism is a forming factor in building an advanced civilization, so that people can live in harmony and in carrying out their respective religious rituals peacefully.